Synergistic impact of Salmonella typhimurium and Eimeria spp. coinfection on turkey poults: Growth performance, salmonella colonization, and ceca microbiota insights - Hamid Reza Rafieian-Naeini; Hanseo Ko; Doyun Goo; Venkata Sesha Reddy Choppa; Seshidhar Reddy Gudidoddi; Hemanth Reddy Katha; Woo Kyun Kim (Poultry Science)
Salmonella contamination in poultry products is a significant concern due to its potential to cause severe economic losses and public health problems. On the other side, coccidiosis is induced by Eimeria (E.) species. involves the destruction of host intestinal epithelial cells and subsequent invasion of pathogens, resulting in performance reduction and enhanced pathogen infection in poultry and economic losses for the poultry industry. A study was conducted to evaluate the impact of Eimeria infection and Salmonella typhimurium (ST) on growth performance, Salmonella colonization, and ceca microbiota in turkey poult. A total of 420 one-day-old male turkey poults were randomly allocated into six treatments, with five replicated cages for each treatment, over a 21-day experimental period. The study followed a 2 × 3 factorial design. Treatments consisted of NC, negative control without any challenge; T1, challenged with 8000 oocysts of E. meleagrimitis and E. adenoeides at d 8; T2, challenged with 16,000 oocysts of E. meleagrimitis and E. adenoeides at d 8; T3, challenged with nalidixic acid-resistant Salmonella typhimurium (ST) at d 0; T4, challenged with ST at d 0 and 8000 oocysts of E. meleagrimitis and E. adenoeides at d 8; T5, challenged with ST at d 0 and 16,000 oocysts of E. meleagrimitis and E. adenoeides at d 8. The Eimeria challenge groups significantly reduced the BW compared to the non-challenge group (P < 0.001). The challenged groups decreased FI during 9–14 days of age (P < 0.01). Salmonella typhimurium did not affect BW entire trial period (P > 0.05). Gut permeability (GP) increased in the challenge groups compared to the NC group (P < 0.001). Both ST and Eimeria significantly decreased superoxide dismutase (SOD) in the liver (P < 0.01). The challenge groups had lower villus height (VH) and higher crypt depth (CD) compared to the NC group, resulting in decreased VH:CD ratio in the duodenum and jejunum (P < 0.01). The groups T1, T2, and T4 had significantly higher fat deposition than the NC group (P < 0.05). The coinfected groups (T4 and T5) had higher salmonella colonization in the spleen compared to the ST-infected group (T3, P < 0.05). The ST challenge significantly decreased alpha diversity, including pielou evenness and Shannon entropy (P < 0.05). The Proteobacteria phylum and Enterobacteriaceae family significantly increased in T5 compared to the NC, T1, T2, and T3 (P < 0.05). In conclusion, Eimeria infection negatively impacted growth, gut health, intestine barrier integrity, and histology, while Salmonella had a milder effect on performance. Coinfection with Salmonella and Eimeria spp. led to changes in gut microbiota and increased liver Salmonella colonization and fat deposition in turkey poults.